PENERAPAN MODEL PEMBELAJARAN KOOPERATIF BERBASIS KEARIFAN LOKAL PANCA STHITHI DARMENG PRABHU UNTUK MENINGKATKAN HASIL BELAJAR AGAMA HINDU - I Nengah Dwi Endra Suanthara; I Dewa Gede Ngurah Diatmika (Jurnal IKA, 2022)
This research was conducted in two cycles, subjects in class XI.P.1. SMK Negeri 1 Kubutambahan additional semester 1 2020/20201academic year with 33 students consisting of 16 men, and 17 women. Based on the research findings obtained significantly from 33 students in the initial reflection of 14 people complete or 42% and an increase in the first cycle to 25 people or 76% and in the second cycle of classical completeness reached 100% or 33 people. This means that the application of cooperative learning models based on local wisdom panca sthithi dabeng prabhu can improve learning outcomes of Hinduism class XI students.